Aggravation factors in children's acute appendicitis - Benedictti, Juan L (Cirugía del Uruguay, 1984)
The most frequent ethiology of children's acule abdomen is appendicitis. The factors that aggravate this disease in childhood are enunciated. Diagnosis basad in a corree! clinical record and physical examination, not always is possible to be done. Taking in account appendicitis accelerated evoluti• vi!y -for the most part in suckling baby and small child- in all acule abdominal pain syndrome, we must think on it.